Microwave-assisted solvent-free tandem cross-metathesis/intramolecular isomerization-cyclization reaction for the synthesis of N-substituted pyrroles: It's computational analysis. Issue 4 (16th February 2022) - Khan, Arif; Siddique, Asher M.; Shaikh, Majeed; Khan, Imran A.; Shafi, Syed
Abstract: The microwave-assisted solvent-free reaction has been developed for the rapid synthesis of different pyrrole derivatives using cross-metathesis (CM) between N -allylamines and α, β-unsaturated carbonyl compounds with moderate to good yields. This method is solvent free, facile, rapid, and high yielding reaction for the synthesis N -substituted pyrrole derivatives. The effect of microwave irradiation versus classical thermal conditions is demonstrated through a series of comparative cross-metathesis reactions. In the present eco-friendly approach, the combination of solvent-free conditions and microwave irradiations leads to a substantial reduction in reaction times with improved yields. The computational analysis revealed that the microwave irradiation conditions favored the interconversion of ruthenacyclobutane (RuG to RuH ) approximately 10-fold more than the conventional heating. Exclusive formation of pyrrole ring system (cyclization- aromatization cascade reaction) over piperazinone (aza-michael product) has been explained through DFT calculations. Graphical Abstract: UF0001